Pregnancy and periodontal disease: Review of the literature (Research, Society and Development, 2022)
Objective: The objective of the study is to determine the relationship and the impact that periodontal diseases have during pregnancy for both the pregnant woman and the fetus. Methodology: An exhaustive search of the literature was carried out in the "PUBMED", "Science Direct", "Scopus" and "Ebsco" databases using the keywords: "Pregnancy", "Periodontal Disease", "Gingivitis", " Periodontitis”; where a total of 20 articles that met the inclusion and exclusion criteria could be obtained. Results: Periodontal disease has serious consequences on the development of the fetus due to the imbalance between the patient's immunity and the presence of pathogenic periodontal microorganisms. Conclusion: Periodontal disease is a risk factor to be taken into account during pregnancy, its early diagnosis and effective treatment will avoid any type of complication in the short or long term.